SERUM GONADOTROPIN PATTERNS (FSH AND LH) IN THE ASSESSMENT OF ABNORMAL UTERINE BLEEDING (Journal of Medical & Health Sciences Review, 2025)
Background: Abnormal uterine bleeding (AUB) is a frequent gynaecological disorder that affects women of reproductive age and accounts for a large proportion of outpatient visits. The FIGO PALM-COEIN system classifies AUB into structural and non-structural causes. Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are key regulators of the menstrual cycle, and their imbalance contributes to abnormal bleeding.Methods:This cross-sectional study included 102 women aged 18–50 years presenting with AUB in gynaecology clinics of Rawalpindi and Islamabad between October 2024 and May 2025. Demographic and clinical data were recorded, AUB was classified using the FIGO system, and serum FSH and LH levels were analysed by immunoassay.Results: Women aged 36–40 years were most affected, with Multiparity and middle socioeconomic background predominating. Structural causes, mainly leiomyomas and polyps, were more common than non-structural causes. Heavy menstrual bleeding was the leading presentation. Elevated FSH and LH were found in 28% and 34% of patients, respectively, while 21% showed an LH/FSH ratio >2.Conclusion:AUB is influenced by both uterine pathology and gonadotropin imbalance. Assessment of FSH and LH may support accurate diagnosis and targeted management.